A Linguistic Analysis of Behavioral Adaptations and Communal Values in The Doll’s House & A Death in the Stadium - Eyvazi, Mojgan (AI and Tech in Behavioral and Social Sciences, 2025)
In spite of human beings’ inherent knowledge of cultural behaviors, most of the content of cultural practices—especially those in common with other cultural identities—remain unnoticeable. The present research represents a detailed statistical analysis of linguistic elements depicting the nature and unique characteristics of such unnoticeable values that result in cultural diversities in the settings of The Doll’s House & A Death in the Stadium. Accordingly, the question under study is whether there exist a set of defined linguistic items representing the social discourse flow and to what extent the literary theorists and language practitioners can use them in the comparison of different texts as explanation facts. In fact, in both texts there are some prominent social values and parallel social conflicts. Three of these social values include wealth, hierarchy and hegemony all of which are investigated in details. Having found all representations of these three values in each of the texts, the paper also quantifies the data to have a better understanding of the analyses. Since not all representations of the items were the same regarding their relation to the items, three various coefficients are applied to give them more acceptable weight.